2009
DOI: 10.1002/pon.1508
|View full text |Cite
|
Sign up to set email alerts
|

Massage therapy reduces physical discomfort and improves mood disturbances in women with breast cancer

Abstract: BACKGROUND. A randomized controlled trial was conducted to investigate the efficacy of classical massage treatment in reducing breast cancer-related symptoms and in improving mood disturbances. METHODS. Women diagnosed with primary breast cancer were randomized into an intervention group and a control group. For a period of 5 weeks, the intervention group received bi-weekly 30-min classical massages in the back and head-neck areas. The control group received no additional treatment to their routine healthcare.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
85
0
13

Year Published

2010
2010
2017
2017

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 97 publications
(104 citation statements)
references
References 56 publications
6
85
0
13
Order By: Relevance
“…This indicates that classical massage also has a certain psychotherapeutic component arising from the therapist"s attention [33]. Further investigation will be necessary to identify to what extent the psychological massage effects can be ascribed to the classical massage itself and what part the relationship to the therapist plays [33,38,42].…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…This indicates that classical massage also has a certain psychotherapeutic component arising from the therapist"s attention [33]. Further investigation will be necessary to identify to what extent the psychological massage effects can be ascribed to the classical massage itself and what part the relationship to the therapist plays [33,38,42].…”
Section: Discussionmentioning
confidence: 97%
“…The patients were treated on a massage table, lying in a prone position. Massage therapy was applied according to a standardized protocol [33]. Stroking, kneading, and frictions were used to massage the following muscles: sternocleidomastoid muscles, trapezius muscles, rhomboid muscles, small neck muscles, supraspinatus muscles, teres major muscles, levator scapulae muscles, autochthonal back muscles, latissimus dorsi muscles, and pectoral muscles.…”
Section: Interventionmentioning
confidence: 99%
“…28 A nonrandomized controlled study of a 20-minute seated massage in young adult psychiatric inpatients found significantly reduced self-reported anxiety and resting heart rate. 29 A larger literature reports benefits following full-body massage in a variety of patient populations and conditions: RCTs of full-body massage in patients report significantly decreased pain and improved function in patients with chronic low back pain; 30 significantly reduced pain, anxiety, and tension in postoperative cardiac patients; 31 significantly increased heart rate variability and improved mood in breast cancer survivors with cancer-related fatigue; 32 significantly reduced pain, increased muscle relaxation, and improved mood in hospice inpatients with metastatic bone pain; 33 significantly reduced depression in patients with breast cancer; 34 significantly decreased physical discomfort and fatigue 35 and perceived stress in breast cancer patients. 36 Significantly reduced pain and anxiety in patients with chronic nonmalignant pain following nurse-administered 15-minute back massage has been reported.…”
Section: Discussionmentioning
confidence: 99%
“…Masaj ile ilgili meme kanserli hastaları ile yapılan iki adet randomize klinik çalışmanın sonuç-ları incelendiğinde; masaj grubunda tüm masajları takiben bulantı deneyiminin dikkat çekici düzeyde azalma bildirilmiştir. [46,47] Myers, Walton, Bratsman, Wilson ve Small'ın 2008 [48] yapmış olduğu metaanalizde masajın, bulantı şiddetini azaltmada etkili olduğu vurgulanmıştır.…”
Section: Terapötik Masajunclassified